Scientific writing and publishing in medicine and health sciences A quick guide in English and German - Cals, Jochen (De Gruyter, 2021)
Writing and publishing scientific papers is the core business of researchers, but is often experienced as difficult and frustrating. This book provides clear and concise key information on 12 major aspects of the process, from how to get started to dealing with reviewers' comments. We describe each aspect structured into background information (''What you should know''), concrete advice (''What you should do''),and a checklist of the main points.